Spatial Variation in Primary Production in the Eastern Indian Ocean - Liu, Haijiao; Song, Yuyao; Zhang, Xiaodong; Zhang, Guicheng; Wu, Chao; Wang, Xingzhou; Thangaraj, Satheeswaran; Wang, Dongxiao; Chen, Ju; Sun, Jun (Frontiers in Marine Science, 2021)
To examine the spatial pattern and controlling factors of the primary productivity (PP) of phytoplankton in the eastern Indian Ocean (EIO), deck-incubation carbon fixation (a 14C tracer technique) and the related hydrographic properties were measured at 15 locations during the pre-summer monsoon season (February–April 2017). There are knowledge gaps in the field observations of PP in the EIO. The estimated daily carbon production rates integrated over the photic zone ranged from 113 to 817 mgC m–2 d–1, with a mean of 522 mgC m–2 d–1. The mixed-layer integrated primary production (MLD-PP) ranged from 29.0 to 303.7 mgC m–2 d–1 (mean: 177.2 mgC m–2 d–1). The contribution of MLD-PP to the photic zone-integrated PP (PZI-PP) varied between 19 and 51% (mean: 36%). Strong spatial variability in the carbon fixation rates was found in the study region. Specifically, the surface primary production rates were relatively higher in the Bay of Bengal domain affected by riverine flux and lower in the equatorial domain owing to the presence of intermonsoonal Wyrtki jets, which were characterized by a depression of thermocline and nitracline. The PZI-PP exhibited a linear (positive) relationship with nutrient values, but with no significance, indicating a partial control of macronutrients and a light limitation of carbon fixation. As evident from the vertical profiles, the primary production process mainly occurred above the nitracline depth and at high photosynthetic efficiency. Phytoplankton (>5 μm), including dinoflagellates, Trichodesmium, coccolithophores, and dissolved nutrients, are thought to have been correlated with primary production during the study period. The measured on-deck biological data of our study allow for a general understanding of the trends in PP in the survey area of the EIO and can be incorporated into global primary production models.